Students’ Perception of the Use of English-Indonesian Code-Switching in Teaching - AR, Atiqah Fajriyani Yacub; Korompot, Chairil Anwar; Sakkir, Geminastiti (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study aims to assess how students’ perceptions of the use of English-Indonesian code-switching at SMP Unggulan Darussalam Barandasi. There are 8 students in the eighth grade who participated in this study. This study is a qualitative descriptive study that uses observation and interviews as data collection techniques. This study uses two theories, namely linguistic theory and sociolinguistic theory. Based on the findings, the data shows that there are 3 stages in finding the effectiveness of language use during the learning process, namely: language use (context of use, type of code-switching, purpose, strategy), effectiveness of using code-switching (contextual appropriateness, skill level, learning evaluation) and students understanding (conceptual understanding, ability to identify and strategy) and there is a comparison of students. Students see code-switching as a tool that facilitates understanding of difficult material. However, students agree that the use of code-switching must be done in a balanced way so as not to reduce the quality of English exposure.